Gas supply module
Patent Information
- Application Number
- CN202280032009.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-11
- Filing Date
- 2022-02-07
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-02-07
Smart Images

Figure CN117222469B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a gas supply module.
[0002] This application claims priority based on Japanese Application No. 2021-80631, filed on May 11, 2021, and invokes all the contents of the aforementioned Japanese application. Background Technology
[0003] In addition to its filtration applications in solid-liquid separation devices, gas supply modules can also be used to remove gases such as oxygen dissolved in liquids, and to supply gases to liquids. For example, gas supply devices are known for manufacturing dissolved water (gas-dissolved water) for cleaning purposes in the electronics manufacturing industry and for household appliances; and for beverage applications, they are known for manufacturing hydrogen water (hydrogen dissolved in pure water) or carbonated water (carbonated water) (carbonated water containing dissolved carbon dioxide).
[0004] As a gas supply module for gas supply or degassing, or a gas supply module that combines both, a gas supply module for gas supply and degassing has been proposed, which has a suction device for drawing gas from the gas supply module and a gas supply device for supplying gas to the gas supply module arranged side by side (see Patent Document 1).
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-217649. Summary of the Invention
[0008] One embodiment of the present invention provides a gas supply module capable of supplying gas to a liquid supplied to the interior of a hollow fiber membrane. The gas supply module comprises: a shell mainly composed of fluororesin; and multiple hollow fiber membranes mainly composed of polytetrafluoroethylene or modified polytetrafluoroethylene, wherein the porosity K [%), average thickness T1 [mm], and average outer diameter D2 [mm] of the hollow fiber membranes satisfy the following relationship (1).
[0009] K / (T1xD2×100)≥2.0···(1) Attached Figure Description
[0010] Figure 1 A schematic cross-sectional view illustrating an embodiment of the gas supply module of the present invention.
[0011] Figure 2 A schematic perspective view illustrating a hollow fiber membrane according to one embodiment of the present invention.
[0012] Figure 3 for Figure 2 A sectional view of the hollow fiber membrane along line AA. Detailed Implementation
[0013] [The problem this invention aims to solve]
[0014] In recent years, gas supply modules have been used in various applications such as semiconductors, food, medical, and wastewater treatment, requiring compactness and improved gas supply performance and chemical resistance.
[0015] The present invention was made in light of the circumstances in which it aims to provide a gas supply module that can be made compact and has excellent gas supply performance and chemical resistance.
[0016] [Effects of the Invention]
[0017] One embodiment of the present invention provides a compact gas supply module with excellent gas supply performance and chemical resistance.
[0018] [Description of embodiments of the present invention]
[0019] First, the embodiments of the present invention will be described.
[0020] One embodiment of the present invention provides a gas supply module capable of supplying gas to a liquid supplied to the interior of a hollow fiber membrane. The gas supply module comprises: a shell mainly composed of fluororesin; and multiple hollow fiber membranes mainly composed of polytetrafluoroethylene or modified polytetrafluoroethylene, wherein the porosity K [%), average thickness T1 [mm], and average outer diameter D2 [mm] of the hollow fiber membranes satisfy the following relationship (1).
[0021] K / (T1×D2×100)≥2.0···(1)
[0022] This gas supply module, using multiple hollow fiber membranes with porosity K [%], average thickness T1 [mm], and average outer diameter D2 [mm] satisfying the relationship in equation (1) above, achieves high gas supply performance and water pressure resistance, and also allows for miniaturization. Furthermore, by having a hollow fiber membrane primarily composed of polytetrafluoroethylene (PTFE) or modified PTFE and a shell primarily composed of fluororesin, it exhibits excellent chemical resistance. Here, "primary component" refers to the component with the highest mass percentage, for example, a component with a mass percentage of 50% or more, preferably 70% or more, and more preferably 95% or more.
[0023] The aforementioned "porosity" refers to the ratio of the total volume of pores to the total volume of the hollow fiber membrane, which can be determined by measuring the density according to ASTM-D-792. The sample's dry mass and water mass were measured in units of 0.0001 g, and the sample volume was calculated from the difference. Furthermore, the true specific gravity of polytetrafluoroethylene (PTFE) was set to 2.17 g / cm³.3 The volume of resin constituting the sample is calculated based on the dried mass. The porosity, expressed as a percentage (%), is the ratio of the void volume (resin volume minus sample volume) to the sample volume. Alternatively, the porosity can be determined in the following order: First, the length (L) of the hollow fiber membrane whose porosity is to be determined is measured in 1 mm units. Next, the weight (W) of the hollow fiber membrane is measured using an electronic balance in 0.0001 g units. Then, based on the above measurements, the porosity [%) is calculated using the following formula.
[0024] Porosity [%] = {1 - Volume of resin only [cm]} 3 ] ÷ Total volume of hollow fiber membrane [cm 3 ]}×100
[0025] ={1-(W[g]÷ρ[g / cm]} 3 ])÷(π(D2 2 [mm 2 ]-D1 2 [mm 2 ])×L[mm]÷1000)}×100
[0026] Here, "ρ" represents the true specific gravity of polytetrafluoroethylene, which is 2.17 g / cm³. 3 ].
[0027] The "average thickness" of the hollow fiber membrane can be obtained by dividing (average outer diameter - average inner diameter) by 2. The "average outer diameter" refers to the average of the outer diameters at any two points when the cross-section of the hollow fiber membrane is circular. When the cross-section of the hollow fiber membrane is elliptical, the diameters of the minor and major axes at two points are measured, and the average value is taken as the average outer diameter. Furthermore, when the cross-section of the hollow fiber membrane is an irregular shape other than a normal circle or ellipse, the edge information of the cross-section is collected and approximated as a circle, and the inner circumference is divided by pi to obtain the average outer diameter. The "average inner diameter" refers to the average of the inner diameters at any two points. Specifically, the average outer diameter can be measured in the following order: First, the hollow fiber membrane is circumferentially cut with a plane perpendicular to the length direction, and the entire cross-section is observed using an electron microscope. The outer diameters at two approximately diagonally opposite positions (approximately 90 degrees phase offset) of the cross-section are measured, and the average value is taken as the average outer diameter (D2).
[0028] The heat of fusion of the hollow fiber membrane is preferably 30 J / g or more and 45 J / g or less. By setting the heat of fusion of the hollow fiber membrane to the above range, a hollow fiber membrane with high crystallinity and a better range of pore size and porosity can be obtained.
[0029] The heat of fusion of the hollow fiber membrane was measured using a differential scanning calorimeter (DSC). The heat of fusion was the heat absorbed between 296°C and 343°C in the third step, as measured by the DSC. Specifically, after the first step of heating from room temperature to 245°C at a rate of 50°C / min, followed by heating from 245°C to 365°C at a rate of 10°C / min; the second step of cooling from 365°C to 350°C at a rate of -10°C / min and holding, followed by cooling from 350°C to 330°C at a rate of -10°C / min, and then cooling from 330°C to 305°C at a rate of -1°C / min; and the third step of cooling from 305°C to 245°C at a rate of -50°C / min, followed by heating from 245°C to 365°C at a rate of 10°C / min, the heat of fusion of the hollow fiber membrane was the heat of fusion between 296°C and 343°C in the third step. The sample volume in the above determination was 10 mg to 20 mg, and the sampling time was 0.5 seconds per measurement.
[0030] Preferably, the hollow fiber membrane has an average outer diameter D2 of 0.70 mm or less, an average inner diameter D1 of 0.32 mm or less, a water pressure resistance of 0.3 MPa or more, and a porosity K of 30% or more. By ensuring that the average outer diameter, average inner diameter, water pressure resistance, and porosity K of the hollow fiber membrane are within the aforementioned ranges, it is possible to construct a bundle of thin-walled hollow fiber membranes with fine diameters, high water pressure resistance, and high porosity. Therefore, it is possible to further miniaturize the gas supply module and improve its gas supply performance.
[0031] The aforementioned "average inner diameter" refers to the average of the inner diameters at any two points. The average inner diameter can be determined in the following order: First, the hollow fiber membrane is circumferentially cut with a plane perpendicular to its length direction, and the entire cross-section is observed using an electron microscope. The inner diameters are measured at two approximately diagonally opposite positions (approximately 90 degrees phase offset) along the cross-section, and the average value is taken as the average inner diameter (D1). The aforementioned "water pressure resistance" refers to the pressure at which water begins to leak from the other side when water pressure is applied to one side of the membrane; it is also called leakage pressure. Generally, the larger the aperture of the through-hole, the easier it is to leak water, and the lower the water pressure resistance; conversely, the smaller the aperture, the higher the water pressure resistance. Specifically, the aforementioned water pressure resistance is determined according to JIS-L1092 (2009). Specifically, the inner cavity of the hollow fiber membrane is filled with water, and the water pressure on the inner cavity is continuously increased at a rate of 100 kPa / min. The pressure at the moment when water droplets leak from the outer surface of the hollow fiber membrane is taken as the water pressure resistance.
[0032] When pure water with a dissolved oxygen concentration of 0.6 ppm or less is supplied to the interior of the hollow fiber membrane, and air is permeated at a pressure of 10 kPa, the maximum flow rate of the pure water after air supply treatment, which can maintain a dissolved oxygen concentration of 8 ppm or more, is preferably 0.035 mL / (cm²) per minute relative to the unit internal surface area of the hollow fiber membrane.2 (minutes) or more. This gas supply module can maintain a dissolved oxygen concentration of 8 ppm or more in the treated pure water. With a maximum flow rate within the above range, it can supply gas to the liquid at a high concentration and flow rate with less membrane area, resulting in superior gas supply performance. Here, "internal surface area" refers to the surface area of the inner side of the hollow fiber membrane.
[0033] The main component of the aforementioned shell is preferably a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, or a combination thereof. By using fluororesin as the main component, the aforementioned shell can improve chemical resistance and mechanical strength.
[0034] [Detailed Description of Embodiments of the Invention]
[0035] Hereinafter, the gas supply modules of various embodiments of the present invention will be described in detail with reference to the accompanying drawings.
[0036] <Gas Supply Module>
[0037] Another embodiment of the gas supply module of the present invention can supply gas to liquid supplied into a hollow fiber membrane. The gas supply module has a housing and multiple hollow fiber membranes. The walls of the hollow fiber membranes can suppress liquid leakage and allow gas permeation. This gas supply module can be applied to applications in any field. It can be applied to applications such as cleaning water for semiconductors, electronic devices, and medical use; food and beverage manufacturing; purification and neutralization of industrial wastewater, river water, lake water, swimming pool water, and public bath water; water treatment applications for beverage water or industrial water; and various applications such as the enrichment function of specific gases such as oxygen, ozone, carbon dioxide, nitrogen, and hydrogen through the permeation of liquids.
[0038] This gas supply module can be used in: an integrated type where the gas supply module is fixed in various devices; and any type of replaceable chuck type where the housing and the membrane component having multiple hollow fiber membranes are independent and the membrane component is inserted into the housing.
[0039] As an example of a gas supply module in one embodiment of the present invention, Figure 1 A gas supply module 3 for supplying gas is shown. The gas supply module 3 has: a membrane member 2 having multiple hollow fiber membranes 1 arranged aligned in one direction; and a cylindrical housing 11 housing the membrane member 2. The gas supply module 3 is of the type that allows gas to pass through the hollow fiber membrane 1 and supplies gas to the liquid supplied to the hollow fiber membrane 1.
[0040] The membrane component 2 has: a first sealing portion 4 that holds one end of a plurality of hollow fiber membranes 1; and a second sealing portion 5 that holds the other end of the plurality of hollow fiber membranes 1. A potting material is filled between the hollow fiber membranes 1 and between the bundle of hollow fiber membranes and the inner surface of the housing in the first sealing portion 4 and the second sealing portion 5.
[0041] The aforementioned potting compound is primarily composed of resin, rubber, or elastomer. There are no particular limitations on the potting compound; examples include epoxy resin, polyurethane resin, UV-curable resin, fluoropolymer, silicone resin, polyamide resin, polyethylene, polypropylene, and other polyolefin resins. Among these, fluoropolymers and silicone resins are preferred from the viewpoint of providing excellent adhesion between hollow fiber membranes primarily composed of polytetrafluoroethylene (PTFE) or modified PTFE and shells primarily composed of fluoropolymers.
[0042] The gas supply module 3 can be configured to have: a cylindrical housing 11; a first sleeve 12 installed on one side of the housing 11, having a joint structure in which a gas supply port 9 and a first sealing part 4 are joined; a first cover 13 sealing the end of the housing 11 on the side of the first sleeve 12, having a liquid outlet 8; a second sleeve 14 installed on the other side of the housing 11, having a joint structure in which a gas outlet 19 and a second sealing part 5 are joined; and a second cover 15 sealing the end of the housing 11 on the side of the second sleeve 14, having a liquid supply port 7.
[0043] The gas supply module 3 has a liquid supply port 7 at one end for supplying raw water in the S1 direction, and a liquid outlet 8 at the other end for discharging liquid that has permeated through multiple hollow fiber membranes 1 in the S2 direction. The housing 11 has a gas supply port 9 for supplying gas in the P1 direction and a gas outlet 19 for discharging gas in the P2 direction on its side. Furthermore, the arrangement and orientation of the gas supply port 9 and the gas outlet 19 are not particularly limited and can be configured according to the state in which the gas supply module 3 is installed.
[0044] Raw water supplied from the liquid supply port 7 into the hollow fiber membrane 1 is then supplied into the housing 11. The treated liquid is then discharged from the liquid outlet 8 located on the side near the other end of the housing 11.
[0045] The gas supply module 3 has a shell with fluororesin as the main component and multiple hollow fiber membranes with polytetrafluoroethylene or modified polytetrafluoroethylene as the main component, which makes it highly resistant to chemicals. Therefore, there is no particular limitation on the type of raw water, and it can use various liquids such as pure water, beverage water, medicine, and wastewater according to the purpose.
[0046] Furthermore, the gas supplied from the gas supply port 9 is drawn into the gas outlet 19 from the wall of the hollow fiber membrane 1, and is discharged from the top of the gas outlet 19 while supplying gas to the liquid supplied to the hollow fiber membrane 1.
[0047] Examples of gases supplied as described above include air, oxygen, carbon dioxide, hydrogen, ozone, nitrogen, hydrogen sulfide, and ammonia.
[0048] The casing 11 is primarily composed of a fluoropolymer. By using a fluoropolymer as the primary component, the casing 11 exhibits excellent chemical resistance. Preferably, the fluoropolymer is a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polytetrafluoroethylene, a tetrafluoroethylene-hexafluoropropylene copolymer, or a combination thereof. By using these fluoropolymers as the primary component, the casing 11 exhibits improved chemical resistance and mechanical strength.
[0049] In this air supply module 3, when pure water with a dissolved oxygen concentration of 0.6 ppm or less is supplied to the interior of the hollow fiber membrane and air is permeated at a pressure of 10 kPa, the maximum flow rate of the pure water after air supply treatment, which can maintain a dissolved oxygen concentration of 8 ppm or more, is preferably 0.035 mL / (cm²) relative to the unit internal surface area of the hollow fiber membrane 1. 2 (minutes) or more. In this gas supply module 3, the pure water after gas treatment can maintain a dissolved oxygen concentration of 8 ppm or more. The maximum flow rate is within the above range, which can efficiently supply high-concentration gas to the liquid, and the gas supply effect is even better.
[0050] Hollow fiber membrane
[0051] Figure 2 and Figure 3 The hollow fiber membrane 1 is mainly composed of polytetrafluoroethylene (PTFE) or modified PTFE. PTFE and modified PTFE are fluoropolymers with excellent chemical and solvent resistance, thus improving the selectivity of the types of liquids and gases supplied to the gas supply module 3. Furthermore, PTFE and modified PTFE are highly hydrophobic fluoropolymers, thus suppressing liquid leakage from the hollow fiber membrane 1 and improving gas permeability.
[0052] Modified polytetrafluoroethylene (PTFE) refers to PTFE copolymerized with hexafluoropropylene (HFP), alkyl vinyl ether (AVE), chlorotrifluoroethylene (CTFE), etc., in small amounts, preferably less than 1 / 50 (molar ratio) relative to tetrafluoroethylene.
[0053] The lower limit of the average outer diameter D2 of the hollow fiber membrane 1 is not particularly limited, but is preferably 0.1 mm, more preferably 0.2 mm. On the other hand, the upper limit of the average outer diameter D2 of the hollow fiber membrane 1 is preferably 0.70 mm, more preferably 0.4 mm. When the average outer diameter D2 does not meet the lower limit, the pressure loss may increase. Conversely, when the average outer diameter D2 is greater than the upper limit, the membrane area housed in the housing 11 may become smaller, or the pressure resistance may decrease, which may lead to rupture caused by internal pressure or deformation caused by external pressure.
[0054] The lower limit of the average inner diameter D1 of the hollow fiber membrane 1 is not particularly limited, but is preferably 0.05 mm, more preferably 0.1 mm. On the other hand, the upper limit of the average inner diameter D1 of the hollow fiber membrane is preferably 0.32 mm, more preferably 0.2 mm. When the average inner diameter D1 does not meet the lower limit, the pressure loss may increase. Conversely, when the average inner diameter D1 is greater than the upper limit, the pressure resistance decreases, and rupture caused by internal pressure and deformation caused by external pressure may occur.
[0055] The lower limit of the average thickness T1 of the hollow fiber membrane 1 is preferably 0.01 mm, more preferably 0.02 mm. On the other hand, the upper limit of the average thickness T1 of the hollow fiber membrane 1 is preferably 0.20 mm, more preferably 0.10 mm. When the average thickness T1 does not meet the lower limit, the pressure resistance decreases, and rupture caused by internal pressure and deformation caused by external pressure may occur. Conversely, when the average thickness T1 is greater than the upper limit, the gas permeability may decrease.
[0056] The lower limit of the porosity K of the hollow fiber membrane 1 is preferably 30%, more preferably 40%. On the other hand, the upper limit of the porosity K of the hollow fiber membrane 1 is not particularly limited, but is preferably 80%, more preferably 70%. When the porosity K of the hollow fiber membrane 1 does not meet the lower limit, the gas permeability decreases, and the gas supply performance of the hollow fiber membrane 1 may decline. When the porosity K of the hollow fiber membrane 1 is greater than the upper limit, the mechanical strength of the hollow fiber membrane 1 may decrease, and damage such as decreased durability and rupture caused by internal pressure may occur.
[0057] The porosity K [%), average thickness T1 [mm] and average outer diameter D2 [mm] of the hollow fiber membrane 1 described above satisfy the following relationship (1).
[0058] K / (T1xD2×100)≥2.0···(1)
[0059] By ensuring that the porosity K [%), average thickness T1 [mm], and average outer diameter D2 [mm] of the hollow fiber membrane 1 satisfy the relationship in equation (1), the gas supply module can achieve high gas supply performance and water pressure resistance, and can be miniaturized. When K / (T1×D2×100) is less than 2.0, the gas supply performance or water pressure resistance of the gas supply module may decrease, and miniaturization may be difficult.
[0060] The lower limit of the average pore size of the hollow fiber membrane 1 is preferably 3.0 nm, more preferably 5.0 nm. On the other hand, the upper limit of the average pore size of the hollow fiber membrane 1 is preferably 50.0 nm, more preferably 40.0 nm. When the average pore size does not meet the lower limit, the gas supply performance may become insufficient. Conversely, when the average pore size is greater than the upper limit, the water pressure resistance decreases, and liquids such as water mixed with impurities such as surfactants may leak out.
[0061] The average pore size was determined using the bubble point method (ASTM F316-86, JIS K3832) with a fine pore size distribution measuring instrument, etc., in the following order. First, the relationship between the differential pressure applied to the membrane and the air flow rate through the membrane was measured using a fine pore size distribution measuring instrument, etc., under both dry and wetted membrane conditions. Then, the resulting graphs were used to create dry and wetted curves, respectively. When the differential pressure at the intersection of the curve obtained by taking half the flow rate of the dry curve and the wetted curve was set as P (Pa), the value of d (nm) expressed by the formula d = cγ / P was the average pore size. Here, c is a constant of 2860, and γ is the surface tension of the liquid (dyn / cm = mN / m).
[0062] As another method, the pore size of hollow fiber membranes can also be determined using the bubble point method of a porosimeter that performs liquid / liquid phase displacement. Furthermore, since PTFE, the main component of hollow fiber membranes, is a hydrophobic resin, the pore size of hollow fiber membranes can also be determined using a pure water porosimeter based on the same principle as a mercury porosimeter, employing the Washburn equation.
[0063] In this gas supply module 3, the water pressure resistance of the hollow fiber membrane 1 is preferably 0.3 MPa or higher, more preferably 1.0 MPa or higher. By ensuring the water pressure resistance of the hollow fiber membrane 1 is within this range, liquid can flow at high pressure in the gas supply module 3. Because the liquid can flow at high pressure in the gas supply module 3, foaming will not occur in the liquid even if the pressure of the supplied gas is increased, thus enabling the production of dissolved gas liquids with higher concentrations.
[0064] The upper limit of the heat of fusion of the hollow fiber membrane 1 is preferably 45 J / g, more preferably 42 J / g. The lower limit of the heat of fusion of the hollow fiber membrane 1 is preferably 30 J / g, more preferably 33 J / g. When the heat of fusion of the hollow fiber membrane 1 is greater than the upper limit, the pore size may increase. On the other hand, when the heat of fusion of the hollow fiber membrane 1 does not meet the lower limit, the porosity may decrease. By using the heat of fusion of the hollow fiber membrane 1 within the above range, a hollow fiber membrane 1 with high crystallinity and a better range of pore size and porosity can be obtained. As described above, after performing the first to third steps, the heat of fusion of the hollow fiber membrane 1 is the heat of fusion from 296°C to 343°C in the third step. By performing the first to third steps described above, and by setting the heat of fusion in the third step (from 296°C to 343°C) to be 30.0 J / g or more and 45.0 J / g or less, the hollow fiber membrane exhibits properties suitable for stretching. Therefore, its deformability is increased, allowing it to exceed the usual yield point initially observed on the load-elongation curve and stretch to the next inflection point before fracture. As a result, a porous hollow fiber membrane with micropore sizes can be obtained. Therefore, the hollow fiber membrane 1 described above is porous and has an average outer diameter of 0.70 mm or less and an average inner diameter of 0.32 mm or less, which are not available in the prior art. It also possesses high porosity K and high water pressure resistance.
[0065] In conventionally used polytetrafluoroethylene (PTFE) for molding, the heat of fusion in the third step, after the first to third steps described above, is less than 30 J / g. Therefore, it can be assumed that the heat of fusion of this resin in the hollow fiber membrane is also less than 30 J / g. Considering the moldability and strength of the molded product in die molding, paste extrusion molding, etc., such a resin can be used. For example, in paste extrusion, in order to ensure uniformity in molding size, mechanical strength, and other qualities, PTFE with a heat of fusion of 20 J / g or less, or around 25 J / g, can be used depending on the molding size, etc. The fact that the heat of fusion of the hollow fiber membrane 1 in the third step, at 296°C to 343°C, is in the range of 30.0 J / g or more and 45.0 J / g or less, is different from existing hollow fiber membranes. Due to this difference, compared with existing hollow fiber membranes, it has higher deformability, significantly better impact absorption, and superior deformation tightness. Furthermore, through the stretching process, a porous hollow fiber membrane with small pore size and high porosity can be obtained.
[0066] The lower limit of the isopropanol bubble point of the hollow fiber membrane 1 is preferably 500 kPa, more preferably 1000 kPa. On the other hand, the upper limit of the isopropanol bubble point of the hollow fiber membrane 1 is not particularly limited. If the isopropanol bubble point of the hollow fiber membrane 1 does not meet the aforementioned lower limit, the liquid retention capacity of the hollow fiber membrane 1 may become insufficient. The "isopropanol bubble point" is a value measured using isopropanol according to ASTM-F316-86, representing the minimum pressure required to extrude liquid from the pores, and is an indicator corresponding to the average pore size.
[0067] The lower limit for the filling rate of the hollow fiber membrane 1 in the gas supply module 3 is preferably 30%, more preferably 40%. On the other hand, the upper limit for the filling rate of the hollow fiber membrane 1 is preferably 70%, more preferably 60%. When the filling rate of the hollow fiber membrane 1 does not meet the lower limit, the gas supply performance of the gas supply module 3 may decrease. Conversely, when the filling rate of the hollow fiber membrane 1 is greater than the upper limit, the hollow fiber membrane 1 may be crushed when filling it into the housing 11, or it may be difficult to fill it into the housing. In this gas supply module 3, by making the filling rate of the hollow fiber membrane 1, which has high porosity and bubble point, 30% or more and 70% or less, excellent gas supply performance is achieved. Here, "hollow fiber membrane filling rate" refers to the filling density of the hollow fiber membrane 1 filled in the shell 11, which is the ratio (%) of the total cross-sectional area occupied by each hollow fiber membrane 1, calculated based on the outer diameter of each filled hollow fiber membrane 1, to the inner cavity cross-sectional area of the shell 11 perpendicular to the length direction of the hollow fiber membrane 1 filled in the shell 11.
[0068] In addition to polytetrafluoroethylene (PTFE) and modified PTFE, the hollow fiber membrane 1 described above may also contain other fluororesins and additives without compromising the desired effects of the present invention. Examples of such additives include inorganic fillers, metal powders, metal oxide powders, and metal sulfide powders, which are used to improve wear resistance, prevent low-temperature flow, and facilitate the formation of pores.
[0069] [Manufacturing method of hollow fiber membrane]
[0070] Next, an example of the manufacturing method for the hollow fiber membrane described above will be explained. The manufacturing method preferably includes: a molding step, in which particles of, for example, polytetrafluoroethylene (PTFE) or modified PTFE are molded into a tubular shape; a sintering step, in which the tubular molded article is heated to above the melting point of PTFE or modified PTFE; a step of cooling the molten resin; and a stretching step, in which the non-porous tubular molded article is stretched to make it porous. In this way, by stretching after molding, the hollow fiber membrane can be formed, thereby achieving a smaller pore size and forming a porous hollow fiber membrane.
[0071] For example, after eliminating intergranular gaps by melting polytetrafluoroethylene or modified polytetrafluoroethylene at a melting point of 30.0 J / g or more and 45.0 J / g or less in the third step above at 296°C to 343°C, the hollow fiber membrane described above can be obtained by slow cooling. That is, the process includes: heating the polytetrafluoroethylene or modified polytetrafluoroethylene to above its melting point to melt it; cooling the molten resin; and / or maintaining the temperature at 313°C or higher and less than 321°C for at least 10 minutes.
[0072] Polytetrafluoroethylene (PTFE) or modified PTFE with a heat of fusion of 30.0 J / g or more and 45.0 J / g or less can be obtained by methods such as irradiating PTFE with a heat of fusion of less than 30.0 J / g with ionizing radiation such as gamma rays, X-rays, ultraviolet rays, or electron beams, or by utilizing a decomposition reaction caused by heating.
[0073] (Molding process)
[0074] In the molding process, polytetrafluoroethylene (PTFE) or modified PTFE powder, manufactured through emulsion polymerization or the like, is molded into a tubular shape to obtain a tubular molded product. PTFE or modified PTFE particles, used as raw materials, refer to powders composed of fine PTFE or modified PTFE particles. PTFE or modified PTFE dispersions, which are emulsions obtained by dispersing these fine PTFE or modified PTFE particles (PTFE or modified PTFE powder) in a liquid (dispersion medium), can also be used as PTFE or modified PTFE powders as raw materials. PTFE or modified PTFE powders are, for example, powders composed of fine PTFE or modified PTFE particles, and examples include fine PTFE or modified PTFE powders manufactured through emulsion polymerization and PTFE or modified PTFE molded powders manufactured through suspension polymerization.
[0075] When molding polytetrafluoroethylene (PTFE) or modified PTFE powder into tubular shapes to obtain tubular articles of a specified shape and size, known methods for molding powder into films can be cited, such as: methods of extruding a paste into tubular shapes after mixing it with an extrusion aid; and methods of molding, drying, and removing the dispersion medium using a PTFE or modified PTFE dispersion (casting method). PTFE or modified PTFE is generally difficult to melt-extrude and difficult to prepare solutions of due to its high melt viscosity; therefore, the methods described above are commonly used.
[0076] (Sintering process)
[0077] In the sintering process, the aforementioned tubular molded article is heated to above the melting point of polytetrafluoroethylene (PTFE) or modified PTFE to obtain a non-porous tubular molded article. Hollow fiber membranes obtained by compacting PTFE or modified PTFE particles manufactured through emulsion polymerization, etc., have pores and voids due to the gaps between particles and the removal of extrusion aids. However, by completely melting the PTFE or modified PTFE powder, these pores and voids disappear, or substantially continuous voids are minimized. As a result, non-porous tubular molded articles can be produced. A non-porous membrane molded article means a membrane with almost no pores penetrating the membrane; specifically, a membrane with a Gurley seconds of 5000 seconds or more is preferred. To completely melt the PTFE or modified PTFE powder to produce a non-porous membrane molded article with a Gurley second large value, heating at a temperature higher than the melting point of the raw material is preferred. Furthermore, to suppress resin decomposition and modification, the heating temperature is preferably below 450°C.
[0078] (Cooling process)
[0079] Following the aforementioned sintering process, a process of slowly cooling the polytetrafluoroethylene (PTFE) or modified PTFE is preferably performed. This cooling process involves: first heating the PTFE or modified PTFE to above its melting point, then slowly cooling it to below its crystallization melting point; or heating it at a temperature slightly lower than the melting point of the PTFE or modified PTFE for a certain period of time (hereinafter sometimes referred to as "isotropic treatment"). This cooling generates crystals in the PTFE or modified PTFE, allowing the resin to reach crystallinity saturation before the subsequent stretching process, thus improving the reproducibility of pore size in the manufacture of porous membranes. Furthermore, during crystallization, a lower cooling rate or a longer isothermal treatment time tends to result in higher crystallinity and a higher heat of fusion. Conversely, a higher cooling rate or a shorter isothermal treatment time tends to result in lower crystallinity and a lower heat of fusion.
[0080] The heat of fusion of hollow fiber membranes depends on the amount of crystals formed, which is affected by the cooling rate. Therefore, in order to obtain the heat of fusion within the aforementioned range, cooling is performed by means of: slow cooling (gradual cooling) and / or holding at a temperature above 310°C and below 325°C for at least 10 minutes. Slow cooling is preferably performed at a cooling rate of -3.0°C / min or less, and more preferably at a rate of -2.0°C / min or less.
[0081] Even if the cooling rate is outside the aforementioned range, crystallization can be promoted by holding the temperature at 310°C or higher but less than 325°C for at least 10 minutes. That is, while slow cooling requires strict temperature control, the heat treatment method based on holding the temperature at a constant temperature does not require strict temperature control and allows for more stable and homogeneous heat treatment. Furthermore, since PTFE or modified PTFE fuses together, it is not possible to slowly cool the product from a temperature above its melting point while it is in a roll form. Instead, the product must be drawn out at a very slow linear speed while the sintering and cooling processes are carried out over a long period. On the other hand, the aforementioned heat treatment method based on holding the temperature at a constant temperature allows for the formation of a roll form after cooling to below the melting point, and crystallization can be promoted in the roll form, thus enabling mass production through large-scale batch processing. Additionally, the process of holding the temperature at 310°C or higher but less than 325°C for at least 10 minutes can be performed during cooling after the aforementioned sintering process, or it can be performed after cooling and then heated to maintain the temperature within the aforementioned range.
[0082] As a raw material, polytetrafluoroethylene or modified polytetrafluoroethylene powder or granules can be used directly, or a material in which the heat of melting of polytetrafluoroethylene powder or granules is adjusted to the above-mentioned range can be used, or a material in which at least one of two or more polytetrafluoroethylene powders or granules having a heat of melting within the above-mentioned range can be used.
[0083] (Stretching process)
[0084] In the stretching process, the resulting non-porous tubular molded article is stretched to become porous. A porous hollow fiber membrane can be obtained by stretching the aforementioned non-porous tubular molded article. In the stretching process, stretching can be performed only along the axial direction, or it can be stretched along both the axial and circumferential directions (radial expansion direction). The stretching ratio in the axial direction can be set, for example, to a factor of 3 or more and 10 or less, and the stretching ratio in the circumferential direction can be set, for example, to a factor of 2 or more and 4 or less. By adjusting the stretching conditions such as the stretching temperature and stretching ratio, the size and shape of the pores in the hollow fiber membrane can be adjusted.
[0085] The aforementioned tensile testing is preferably performed on the load-elongation curve between the initial, usual yield point (hereinafter also referred to as the "first yield point") and the next inflection point (hereinafter also referred to as the "second yield point") that occurs before fracture.
[0086] According to the above-described method for manufacturing hollow fiber membranes, hollow fiber membranes with excellent gas supply performance and chemical resistance can be manufactured.
[0087] [Other Implementation Methods]
[0088] The embodiments disclosed in this specification should be considered exemplary in all respects and not restrictive. The scope of the invention is not limited to the configuration of the above embodiments, but is indicated by the scope of the claims, and is intended to include all modifications within the meaning and scope equivalent to the scope of the claims.
[0089] For example, in the above embodiment, the gas supply module is one that fills the hollow fiber membrane with liquid and supplies gas to the liquid. However, it can also be a gas supply module that supplies gas to the hollow fiber membrane or supplies gas to liquid filling the hollow fiber membrane. Regardless of whether the gas supply module supplies liquid to the hollow fiber membrane or supplies gas to the hollow fiber membrane, it has the same gas supply performance.
[0090] Example
[0091] The present invention will be further described in detail below through embodiments, but the present invention is not limited to these embodiments.
[0092] [Determination of physical properties]
[0093] First, the methods for determining the physical properties performed in the following examples and comparative examples will be described.
[0094] (Determination of heat of fusion)
[0095] Take a 10mg to 20mg sample and seal the PTFE in an aluminum bath as needed. It is important to keep the PTFE in a free state so that it can shrink and deform as much as possible, thus preventing the bath from being broken or completely crushed.
[0096] The sample was heated and cooled under the following conditions.
[0097] After heating from room temperature to 245°C at a rate of 50°C / min, heat from 245°C to 365°C at a rate of 10°C / min (first step).
[0098] Next, after cooling from 365°C to 350°C at a rate of -10°C / min and holding, the temperature is further cooled from 350°C to 330°C at a rate of -10°C / min, and then further cooled from 330°C to 305°C at a rate of -1°C / min (second step).
[0099] Next, after cooling from 305°C to 245°C at a rate of -50°C / min, heat from 245°C to 365°C at a rate of 10°C / min (third step).
[0100] Sampling was performed every 0.5 seconds using a Shimadzu Corporation DSC-60A differential scanning calorimeter to determine the heat absorption and release. The heat absorption in the first step was calculated by integrating the interval from 303°C to 353°C; the heat release in the second step was calculated by integrating the interval from 318°C to 309°C; and the heat absorption in the third step was calculated by integrating the interval from 296°C to 343°C. The heat absorption in the third step was taken as the heat of fusion.
[0101] (Porosity)
[0102] The dry mass and water mass of the sample were determined, and the sample volume was calculated from the difference between them. Furthermore, the true specific gravity of PTFE was set to 2.17 g / cm³. 3 The volume of resin constituting the sample is determined from the dried mass. The porosity, expressed as a percentage, is the ratio of the void volume (resin volume removed from the sample volume) to the sample volume.
[0103] (Isopropyl alcohol (IPA) bubble point)
[0104] Hollow fiber membranes are impregnated / soaked in an isopropanol container, filling the pores of the tube wall with isopropanol. Then, air pressure is gradually applied from the inside of one end face of the hollow fiber membrane while it is impregnated. The pressure at which bubbles first escape from the opposite end face is taken as the bubble point. The maximum pressure measured at this time is 500 kPa.
[0105] (Average aperture)
[0106] The porosity was determined using the Washburn formula with a pressure-pure water porosity meter.
[0107] (0.3MPa water pressure test)
[0108] Fill the inner cavity of the hollow fiber membrane with water, and continuously increase the water pressure in the inner cavity to 0.3 MPa at a rate of 100 kPa / min. Observe the leakage of water droplets from the outer surface of the hollow fiber membrane.
[0109] <Hollow Fiber Membrane Tests No. 1 and No. 2 (Examples)>
[0110] [Preparation of raw material powder]
[0111] The following PTFE fine powder is used as the raw material. The PTFE fine powder used here refers to a powder formed by drying and granulating a substance (emulsion polymerization product) composed of the following PTFE particles (primary particles) to a particle size of several hundred μm to several thousand μm. The PTFE particles are PTFE particles with a particle size of 0.15 μm to 0.35 μm generated by emulsion polymerization of tetrafluoroethylene.
[0112] The raw material resins used in Test No. 1 and Test No. 2 are as follows.
[0113] Test No. 1 (Daikin Industries, Ltd. F208: Modified PTFE)
[0114] Experiment No. 2 (Irradiation of CD-123E manufactured by AGC Corporation with 1.0 kGy of gamma rays: homopolymer PTFE)
[0115] The heat of fusion for the third step of each raw material is shown in Table 1.
[0116] [Molding Process]
[0117] The obtained PTFE powder was formed into a tubular shape under the following conditions. Methods for forming the tubular shape include, for example, the paste extrusion method and plunger extrusion method described in the "Fluoropolymer Handbook" (written by Takaomi Satokawa, Nikkan Kogyo Hosha). In Tests No. 1 and No. 2, the aforementioned paste extrusion method was used. 23 parts by weight of a liquid lubricant ("Solvent naphtha", manufactured by Fujifilm and Kojun Pharmaceutical Co., Ltd.) was mixed with the PTFE powder, pressed into a cylindrical shape using a preforming machine, and then extruded into a reel shape using an extruder. The barrel and die temperature was 50°C. Test No. 1 used an extruder with a barrel diameter of 40 mm, a mandrel diameter of 10 mm, a die diameter of 1.0 mm, a core pin diameter of 0.5 mm, and a reduction ratio of 2000. Experiment No.2 used an extruder with a barrel diameter of 30mm, a mandrel diameter of 10mm, a die diameter of 0.8mm, a core pin diameter of 0.4mm, and a compression ratio of 1667.
[0118] [Drying Process]
[0119] In the drying process, the liquid lubricant is dried in a hot air circulating thermostat bath at 200°C.
[0120] [Sintering process]
[0121] The tubular molded product is heated to a furnace temperature of 420°C, above the melting point of PTFE or modified PTFE, using a continuous stretching sintering machine, and sintered at a stretching ratio of 0.9 times to obtain a translucent, non-porous tube.
[0122] [Slow cooling process]
[0123] The translucent, non-porous tube was rolled into a reel and placed in a hot air circulating constant temperature bath and heated at 350°C for more than 5 minutes. It was then continuously and slowly cooled to below 300°C at a cooling rate of less than -1°C / minute.
[0124] [Stretching Process]
[0125] In the stretching process, the obtained non-porous tubular molded product is stretched under the following conditions to obtain a porous tubular molded product. Tensile testing was performed in a tensile testing machine (Autograph AG500 with a thermostatic bath manufactured by Shimadzu Corporation) with a chuck width of 10 mm, a stretching speed of 500 mm / min, and a temperature of 170°C. Furthermore, the average outer diameter and average inner diameter at any two points were measured to obtain the average value, and the average thickness was calculated using the mathematical formula (average outer diameter - average inner diameter) / 2 at any two points.
[0126] The axial stretch ratio of the hollow fiber membranes for each test number is shown in Table 1, and the average outer diameter D2, average inner diameter D1, and average thickness T1 are shown in Table 2.
[0127] <Hollow Fiber Membrane Test No. 3 (Comparative Example)>
[0128] Liquid lubricant (solvent oil manufactured by Fujifilm and Kojun Pharmaceutical Co., Ltd.) was mixed with PTFE powder as the raw material powder as shown below and pressed solid. The paste was then extruded into a tube to produce a tubular molded body. At this time, 19 parts by weight of liquid lubricant were added. The extruded molded product was heated to 200°C and dried to remove the liquid lubricant, resulting in an unsintered tube. Then, it was stretched along the long side at 280°C using a continuous stretching sintering machine to make it porous, and then sintered at 380°C, thereby producing a porous tubular molded body. The temperature of the die used for extrusion molding in Test No. 3, the axial stretching ratio in the stretching process are shown in Table 1, and the average outer diameter D2, average inner diameter D1, and average thickness T1 are shown in Table 2. CD123E (homopolymer PTFE) manufactured by AGC Co., Ltd. was used as the raw material resin for Test No. 3. In addition, the heat of melting of the raw material resin in the third step of Test No. 3 is shown in Table 1.
[0129] The extrusion conditions for the hollow fiber membranes of Tests No. 1 to No. 3 are shown in Table 1. In addition, the results of the determination of porosity K, isopropanol bubble point and average pore size, the results of the 0.3 MPa water pressure test, and the calculation results of K / (T1×D2×100) are shown in Table 2.
[0130] [Table 1]
[0131]
[0132] [Table 2]
[0133]
[0134] <Gas supply module test No. 11 to test No. 14 (hollow fiber membrane test No. 1 to test No. 3)>
[0135] Air supply modules (tests No. 11 to No. 14) with hollow fiber membranes of test No. 1 to test No. 3 were fabricated. In these air supply modules, the hollow fiber membrane fill rate was 40%, and they were manufactured in two sizes: one with a large inner diameter and the other with a small effective length. Four air supply modules with different numbers of hollow fiber membranes were fabricated. Furthermore, these air supply modules used a shell primarily composed of fluororesin. The shell volume, the number of hollow fiber membranes, and the fill rate of the air supply modules are shown in Table 3. The shell volume was calculated by multiplying the inner cross-sectional area of the cylinder by the effective length.
[0136] [Gas Supply Module Performance Evaluation]
[0137] At room temperature of 25°C, pure water with a dissolved oxygen concentration of 0.6 ppm was passed through the hollow fiber cavity of the aforementioned air supply module while being purged with air at a gauge pressure of 10 kPa, and the air supply performance of the air supply module was evaluated. The pure water flow rate was gradually increased from 0.5 ml / min, and the maximum flow rate per minute that could maintain a dissolved oxygen concentration of 8 ppm or higher after air supply was defined as the maximum flow rate per minute achieving 8 ppm. The maximum flow rate per minute that could maintain a dissolved oxygen concentration of 8 ppm or higher, and the maximum flow rate per minute per unit internal surface area of the aforementioned air supply module that could maintain a dissolved oxygen concentration of 8 ppm or higher, are shown in Table 3.
[0138] [Table 3]
[0139]
[0140] Table 3 shows that test modules No. 11 to No. 13, which use polytetrafluoroethylene (PTFE) or modified PTFE as the main component and have hollow fiber membranes with porosity K [%), average thickness T1 [mm], and average outer diameter D2 [mm] satisfying K / (T1×D2×100)≥2.0, can achieve high processing capacity. In particular, test module No. 13, which has a hollow fiber membrane of No. 2 with the aforementioned high K / (T1×D2×100) value, has a very high processing capacity per unit internal surface area. On the other hand, test module No. 14, which has a hollow fiber membrane that does not satisfy K / (T1×D2×100)≥2.0, has a poor processing capacity per unit internal surface area. Furthermore, compared with test module No. 12, which has the same internal volume, test module No. 14 has a very low maximum flow rate of pure water with a dissolved oxygen concentration of 8 ppm or higher.
[0141] As described above, this gas supply module exhibits excellent gas supply performance and chemical resistance. Therefore, this gas supply module is suitable for gas supply devices in semiconductor manufacturing processes, wastewater treatment, beverage and food manufacturing processes, pharmaceutical manufacturing processes, and the like.
[0142] Explanation of reference numerals in the attached figures
[0143] 1: Hollow fiber membrane
[0144] 2: Membrane components
[0145] 3: Gas supply module
[0146] 4: First sealing part
[0147] 5: Second sealing part
[0148] 7: Liquid supply port
[0149] 8: Liquid discharge port
[0150] 9: Gas supply port
[0151] 19: Gas exhaust outlet
[0152] 11: Shell
[0153] 12: First sleeve
[0154] 13: First cover
[0155] 14: Second sleeve
[0156] 15: Second cover
Claims
1. A gas supply module capable of supplying gas to liquid supplied to the interior of a hollow fiber membrane. The gas supply module has: A shell primarily composed of fluororesin; and A hollow fiber membrane with polytetrafluoroethylene or modified polytetrafluoroethylene as the main component. The heat of fusion of the hollow fiber membrane is 30 J / g or more and 45 J / g or less. The heat of fusion of the hollow fiber membrane is the heat of fusion of 296°C to 343°C in the third step following the steps described below: a first step of heating from room temperature to 245°C at a rate of 50°C / min, followed by heating from 245°C to 365°C at a rate of 10°C / min; a second step of cooling from 365°C to 350°C at a rate of -10°C / min and holding, followed by cooling from 350°C to 330°C at a rate of -10°C / min, and then cooling from 330°C to 305°C at a rate of -1°C / min; and a third step of cooling from 305°C to 245°C at a rate of -50°C / min, followed by heating from 245°C to 365°C at a rate of 10°C / min. The hollow fiber membrane has an average outer diameter D2 of less than 0.4 mm, an average inner diameter D1 of less than 0.32 mm, an average thickness T1 of less than 0.10 mm, a water pressure resistance of more than 0.3 MPa, and a porosity K of more than 40%. The porosity K [%], average thickness T1 [mm], and average outer diameter D2 [mm] of the hollow fiber membrane satisfy the following relationship (1). 。 2. The gas supply module according to claim 1, wherein, When pure water with a dissolved oxygen concentration of less than 0.6 ppm is supplied to the interior of the hollow fiber membrane, and air is permeated at a pressure of 10 kPa, the purified water after air supply treatment can maintain a dissolved oxygen concentration of more than 8 ppm. The maximum flow rate per minute relative to the unit internal surface area of the hollow fiber membrane is 0.073 mL / (cm²). 2 (minutes or more) 3. The gas supply module according to claim 1 or 2, wherein, The main components of the shell are tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, or combinations thereof.
Citation Information
Patent Citations
Refrigerator and deairing / air supplying unit
JP2016217649A
Bamboo drain material and liquefaction countermeasure construction method
JP2021080631A
Manufacture of membrane type artificial lung
JP1992236961A
Hollow fiber membrane and hollow fiber membrane module
WO2020084930A1